FOMO vs. JOMO (Joy of Missing Out): The Psychological Conflict of Overly Frequent Running Event Participants - Riu, Isma Azis (Journal Management & Economics Review (JUMPER), 2025)
This qualitative study examines the psychological tension between Fear of Missing Out (FOMO) and Joy of Missing Out (JOMO) among recreational runners in Makassar, Indonesia. Through phenomenological analysis of 15 in-depth interviews and ethnographic observations at local running events, the research reveals how social media, cultural norms, and commercialized race marketing create compulsive participation patterns. Findings indicate that 82% of runners experience FOMO-driven event registration despite financial or physical strain, while a growing minority (38%) embraces JOMO through intentional disengagement strategies like lari buta (non-competitive runs). The study identifies three key conflict areas: (1) gendered pressures for performance visibility, (2) marital status-based participation disparities, and (3) cultural event fatigue—a novel concept describing exhaustion from maintaining running-related social capital. These insights contribute to global sports psychology literature by contextualizing FOMO/JOMO dynamics within Southeast Asia's collectivist fitness cultures. Practical recommendations encourage balanced running engagement through community-led initiatives and culturally-sensitive event design.